Women and Money: Unique Issues – So You Want to Remarry? - Diann Douglas; Martie Gillen; Lynda Spence (EDIS, 2013)
Whether widowed or divorced, if a second marriage is in your future, it may be advisable to look before you leap. Second marriages have a higher failure rate than first marriages. They are often more complex and have stresses not found in many first marriages. Take your time to consider all of the financial circumstances between you and your future spouse before you remarry. This 3-page fact sheet was written by Diann Douglas, Martie Gillen, and Lynda Spence, and published by the UF Department of Family Youth and Community Sciences, March 2013.